IMPROVING VOCATIONAL HIGH SCHOOL ALUMNI COMPETITIVENESS THROUGH ONLINE BUSINESS TRAINING - Nurmawati Nurmawati; Sri Nurhayati; Agus Hasbi Noor (IKIP Siliwangi Bandung, 2021)
This study aims to determine the implementation of online business training carried out at SMK Cendekia Batujajar, West Bandung Regency and to increase the competence of online business alumni who have attended the training. The subjects in this study were the Bursa Kerja Khusus (BKK) of SMK Cendekia Batujajar, the training organizing committee, and the training participants. This study uses a qualitative descriptive method, with data collection techniques through observation, interviews, and documentation studies. From the data analysis and research results, it can be concluded that the online business competence of SMK alumni increases after attending the training. The implementation of online business training at the Batujajar Cendekia Vocational School is based on the BKK analysis of the Batujajar Cendekia Vocational School on the needs of alumni to increase competitiveness in the era of the industrial revolution 4.0, planned program planning according to the conditions and needs of the industrial world.